TENUN LEJO SEBAGAI PRODUK PARIWISATA KHAS KABUPATEN BENGKALIS - Rahmadhani, Sherina Suci; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Indonesia has a diversity of cultures, one of which is the culture in Bengkalis district, namely lejo weaving. In essence, the tourism product is the entire service received and felt by tourists from the time they leave their place of residence to the tourist destination they choose and until they return home where they originally departed. This research aims to determine lejo weaving as a typical tourism product in Bengkalis district. This research uses a qualitative method with a descriptive approach to describe the actual situation by collecting information data directly from the field. The key informants for this research are the head of the Bengkalis district tourism office, the head of Sebauk village, the Putri Mas weaving manager, weaving craftsmen, and consumers. This research uses data collection techniques from literature study, observation, documentation and interviews. The results of this research show that lejo weaving is a tourism product and makes lejo weaving a typical souvenir of Bengkalis district. Keywords: Weaving, Lejo